Application of H(·, ·)-Cocoercive Operators for Solving a System of Variational Inclusions: Rais Ahmad, Mohd Dilshad - Team, Support (Thai Journal of Mathematics, 2012)
In this paper, we apply H(・, ・)-cocoercive operators for solving a system of variational inclusions. By using the resolvent operator technique associated with H(・, ・)-cocoercive operators, we define an iterative algorithm for solving a system of variational inclusions. Convergence criteria is also discussed. Some examples are given in support the definition of H(・, ・)-cocoercive operators.